2021
DOI: 10.1038/s41467-021-22804-x
|View full text |Cite
|
Sign up to set email alerts
|

Co-evolution of tumor and immune cells during progression of multiple myeloma

Abstract: Multiple myeloma (MM) is characterized by the uncontrolled proliferation of plasma cells. Despite recent treatment advances, it is still incurable as disease progression is not fully understood. To investigate MM and its immune environment, we apply single cell RNA and linked-read whole genome sequencing to profile 29 longitudinal samples at different disease stages from 14 patients. Here, we collect 17,267 plasma cells and 57,719 immune cells, discovering patient-specific plasma cell profiles and immune cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 83 publications
(48 reference statements)
2
76
0
Order By: Relevance
“…Since immune cells share the same metabolic requirements with myeloma cells, metabolic competition is created. During the disease course from asymptomatic to symptomatic and relapsing myeloma, the immune microenvironment is highly dynamic and changes in the immune signatures also result in changes in the metabolic profile [ 62 ]. Cancer cells, through hypoxia and lactate increase, have better access to nutrients, which promotes tumor survival and inhibits immune surveillance [ 63 ].…”
Section: Immune Cells Metabolic Disordersmentioning
confidence: 99%
“…Since immune cells share the same metabolic requirements with myeloma cells, metabolic competition is created. During the disease course from asymptomatic to symptomatic and relapsing myeloma, the immune microenvironment is highly dynamic and changes in the immune signatures also result in changes in the metabolic profile [ 62 ]. Cancer cells, through hypoxia and lactate increase, have better access to nutrients, which promotes tumor survival and inhibits immune surveillance [ 63 ].…”
Section: Immune Cells Metabolic Disordersmentioning
confidence: 99%
“…We found that there were significant differences in immune cell infiltration, immune-related functions, immune-related pathways and the expression of immune checkpoint genes between the two groups. Several single-cell transcriptional studies have revealed that transcriptional programs are associated with aggressive myeloma progression and immune evasion (Ryu et al, 2020;Liu et al, 2021). According to the above findings, we present the hypotheses that the prognostic characteristic genes are highly associated with different immune microenvironments in the two groups.…”
Section: Discussionmentioning
confidence: 64%
“…As far as the relationship between immune response, inflammation, and mutational status, MM subjects with the same genetic alterations are inclined to have both plasma cells and immune cells clustered together [140].…”
Section: Mutational Status Inflammation and MM Progressionmentioning
confidence: 99%